2004
DOI: 10.3390/90800627
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Replacement of the Hydroxy by an Amino Group in 4 Hydroxycoumarin and 4-Hydroxy-6-methyl-2-pyrone under Microwave Irradiation

Abstract: Abstract:The reaction of 4-hydroxycoumarin (1) with some primary amines 2a-h and morpholine (2i) under microwave irradiation occurred without opening of the lactone ring to give N-substituted 4-aminocoumarins 3a-i in excellent yields. Under the same experimental conditions, 4-hydroxy-6-methyl-2-pyrone (4) reacted with benzylamine (2e) or 2-phenylethylamine (2f) to give the corresponding N,N'-disubstituted 4-amino-6-methyl-2-pyridones 5e,f. The main advantages of this procedure are dramatically shortened reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the hydroxyl group can be selectively replaced by the amino group of primary and secondary amines, as illustrated in the syntheses of compounds 36 and 37 under previously reported conditions. [27] It is worth mentioning that 4-aminocoumarins exhibit outstanding bioactivities. [28] Finally, the reaction of 5 with POCl3 furnished 4-chlorocoumarin 38 in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the hydroxyl group can be selectively replaced by the amino group of primary and secondary amines, as illustrated in the syntheses of compounds 36 and 37 under previously reported conditions. [27] It is worth mentioning that 4-aminocoumarins exhibit outstanding bioactivities. [28] Finally, the reaction of 5 with POCl3 furnished 4-chlorocoumarin 38 in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…In solution, the likely tautomeric forms of 4-hydroxycoumarin are 2‑hydroxy‑4-chromenone (A) and 2, 4-chromandione (B) [28] . Indeed, synthesis of L TA is carried out via nucleophilic attack of NH 2 group of 3-picolylamine on the C10 carbonyl of 2, 4-chromandione with elimination of water molecule [ 29 , 30 ], according to the following detailed mechanism:
Scheme 1 Synthesis mechanism of ligand (L TA ).
…”
Section: Methodsmentioning
confidence: 99%
“…4 In the study of the reaction of 3 acetyl 4 hydroxy coumarin 2 with benzylamine 4a, we found that the reac tion pathway depends on the solvent nature and the reac tion time. For instance, coumarin 2 reacted with benzyl amine in acetonitrile at room temperature, giving salt 7 in 0.5 h (Scheme 2, path b), which is analogous to salt 5 (see Scheme 1).…”
mentioning
confidence: 99%
“…Opening of the α pyrone ring into 3 hydroxy 3 (2 hydroxyphenyl)prop 2 enamides is also possible. 4 It is also known 5 that primary amines react with 3 acetyl 4 hydroxycoumarin at its acetyl substituent. Modification of fluorine containing 4 hydroxycoumarins have not been studied hitherto.…”
mentioning
confidence: 99%
See 1 more Smart Citation